2020
DOI: 10.1098/rspb.2019.2454
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing adaptive cancer therapy: dynamic programming and evolutionary game theory

Abstract: BACKGROUND: Recent clinical trials have shown that the adaptive drug therapy can be more efficient than a standard MTD-based policy in treatment of cancer patients. The adaptive therapy paradigm is not based on a preset schedule; instead, the doses are administered based on the current state of tumor. But the adaptive treatment policies examined so far have been largely ad hoc. In this paper we propose a method for systematically optimizing the rules of adaptive policies based on an Evolutionary Game Theory mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 65 publications
1
64
0
Order By: Relevance
“…They adopted optimal control theory and showed analytically that to reduce the tumor volume while preserving its heterogeneity, one needs to apply lower than the MTD of drugs. Gluzman et al optimize treatment in the matrix model of interactions between glycolytic and acidic cells, introduced by Kaznatcheev et al (2017) [74]. The total drug usage and time to recovery are optimized, by solving the corresponding Hamilton–Jacobi–Bellman (HJB) equation, similarly to [48].…”
Section: Game Theory Of Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They adopted optimal control theory and showed analytically that to reduce the tumor volume while preserving its heterogeneity, one needs to apply lower than the MTD of drugs. Gluzman et al optimize treatment in the matrix model of interactions between glycolytic and acidic cells, introduced by Kaznatcheev et al (2017) [74]. The total drug usage and time to recovery are optimized, by solving the corresponding Hamilton–Jacobi–Bellman (HJB) equation, similarly to [48].…”
Section: Game Theory Of Cancer Treatmentmentioning
confidence: 99%
“…Additionally, there is evidence for selection for evolvability in tumor cells, e.g., hyper-mutators [37]. Recent works showed that a game-theoretic approach may help to provide an alternative to MTD, based on anticipating and steering the cancer eco-evolutionary dynamics in response to the treatment [74, 137].…”
Section: Introductionmentioning
confidence: 99%
“…The ‘evolutionary stable therapies’ attempt to maintain a stable polymorphic tumor composition of cells sensitive and resistant to therapy, in order to prolong treatment efficacy and progression free survival [ 36 , 37 ]. Previous mathematical studies have developed examples of evolutionary stable therapies, by focusing only on stabilization of the frequency dynamics, while generally ignoring the density dynamics [ 38 , 39 ]. Stabilization of only the underlying frequency dynamics is inadequate in the case of long term stabilization of a growing tumor where tumor cell density is paramount to patient health [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of administering high dosages for a long period of time as an aggressive treatment versus a moderate strategy with low dosages in short duration has been compared through empirical studies [5]. In [6], the authors propose an adaptive therapy that is optimized based on an evolutionary game theoretic Abbreviations PKPD, pharmacokinetic/pharmacodynamic; MTD, maximum tolerated dose; MIC, minimum inhibiting concentration.…”
Section: Introductionmentioning
confidence: 99%